Production and Functional Characterization of a Recombinant Predicted Pore-Forming Protein (TVSAPLIP12) of Trichomonas vaginalis in Nicotiana benthamiana Plants - Diaz, Nicia; Lico, Chiara; Capodicasa, Cristina; Baschieri, Selene; Dessì, Daniele; Benvenuto, Eugenio; Fiori, Pier Luigi; Rappelli, Paola (Frontiers in Cellular and Infection Microbiology, 2020)
Pore-forming proteins (PFPs) are a group of functionally versatile molecules distributed in all domains of life, and several microbial pathogens notably use members of this class of proteins as cytotoxic effectors. Among pathogenic protists, Entamoeba histolytica and Naegleria fowleri display a range of pore-forming toxins belonging to the Saposin-Like Proteins (Saplip) family: Amoebapores and Naegleriapores. Following the genome sequencing of Trichomonas vaginalis, we identified a gene family of 12 predicted saposin-like proteins (TvSaplips): this work focuses on investigating the potential role of TvSaplips as cytopathogenetic effectors. We provide evidence that TvSaplip12 gene expression is potently upregulated upon T. vaginalis contact with target cells. We cloned and expressed recombinant TvSaplip12 in planta and we demonstrate haemolytic, cytotoxic, and bactericidal activities of rTvSaplip12 in vitro. Also, evidence for TvSaplip subcellular discrete distribution in cytoplasmic granules is presented. Altogether, our results highlight the importance of TvSaplip in T. vaginalis pathogenesis, depicting its involvement in the cytolytic and bactericidal activities during the infection process, leading to predation on host cells and resident vaginal microbiota for essential nutrients acquisition. This hence suggests a potential key role for TvSaplip12 in T. vaginalis pathogenesis as a candidate Trichopore.